إنعكاس إدارة علاقات الزبون في تعزيز سمعة المنظمة : دراسة إستطلاعية لعينة من المصارف العراقية الخاصة في مدينة بغداد - الدليمي، عراك عبود عمير; صلاح، أحمد ضياء الدين (جامعة الأنبار - كلية الإدارة والاقتصاد, 2017)
يهدف البحث إلى تحديد تأثير إدارة علاقات الزبون المحتمل في تعزيز سمعة المنظمة، إذ قدم البحث اطار نظري حول مساهمات الباحثين في متغيرات البحث، فضلاً عن الاطار العملي المتمثل بتحليل طبيعة علاقة الارتباط والتأثير بين كل من إدارة علاقات الزبون بوصفه متغيراً مستقلاً والمتمثل ب (رضا الزبون، ولاء الزبون، وقيمة الزبون)، وسمعة المنظمة بوصفها متغيراً تابعا في عدد من المصارف العراقية الخاصة في مدينة بغداد، وهو ما دفع الباحثان إلى بناء نموذج فرضي للبحث تضمن مجموعة من الفرضيات الرئيسية والفرعية، وتمثلت عينة البحث ب(80) مديراً موزعين في مستويات تنظيمية مختلفة، واستخدام الباحثان الاستبانة كأداة لجمع البيانات فضلاً عن المقابلات الشخصية، وتم الاعتماد على برنامج SPSS)) لتحليل هذه البيانات، وكانت أهم الاستنتاجات أن هناك اهتمام بإدارة علاقات الزبون في المصارف العراقية الخاصة، ويعود ذلك إلى اهتمام هذه المصارف ب (رضا الزبون، ولائه، وقيمته)، كما ظهرت سمعة المنظمة في المصارف العراقية الخاصة بمستوى جيد ويعود ذلك إلى اهتمام المصارف الخاصة ب (المسؤولية الاجتماعية، جاذبية المنظمة، جودة الخدمة، الموثوقية، المهارات الإبداعية، والأداء المالي).
This research aims to determine the impact of the customer relationship management in enhancing the reputation of the Organization, providing a theoretical research on the contributions of researchers in the search variables, as well as the practical framework to analyze the nature of the relationship and influence among both customer relationship management as an independent variable of (customer satisfaction, customer loyalty, customer value), and the Organization's reputation as a variable number of Iraqi private banks in the city of Baghdad, prompting the researchers to build a prescriptive model for research included a series of key assumptions And, research sample consisted of (80) as distributors in the different organizational levels, the researchers used a questionnaire as a tool for collecting data as well as personal interviews, and has been relying on SPSS program to analyze this data, and the main conclusions were that there was interest in customer relationship management in private Iraqi banks, due to the interest of these banks (customer satisfaction, loyalty, and its value), the reputation of the Organization in the Iraqi banks for good due to your banks interest (social responsibility, appealing organization, quality of service, reliability, creative skills, And financial performance).
Keywords: السياسة المالية -- النظام المالي -- الأجهزة المصرفية -- المصارف العراقية -- العلاقات العامة -- الزبائن -- بغداد -- العراق -- المجتمع العراقي -- مستخلصات الأبحاث